Asymmetric cost pass-through: An analysis of 21 industrial activities in Brazil from 1996 to 2014 - Débora Pimentel; André de Melo Modenesi; Eduardo Pontual Ribeiro; Camila Cabral Pires-Alves (EconomiA, 2020)
This paper investigates the existence of asymmetric transmission from industrial costs to prices (IPA/FGV) in Brazil from 1996 to 2014. We construct cost indices based on intermediate consumption of industrial activities from the National Accounts (SCN/IBGE). The paper estimates symmetric and asymmetric SVAR models for 21 industrial activities using a decomposition of industrial costs into positive and negative changes. The results of the pass-through estimates indicate that the magnitude of the cost pass-through is heterogeneous among industrial activities. The estimates and Wald tests on the asymmetrical model coefficients show that most industrial activities exhibit positive asymmetric price transmission, i.e., cost increases have a larger pass-through rate than cost decreases.
Keywords: E31; D43; 330; Asymmetric price transmission; Cost pass-through; SVAR; Brazil